Internet Addiction among Secondary School Students in Kota Bharu, Kelantan, Malaysia. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
This present study aims to identify the level of Internet Addiction (IA) on the behavior of secondary school students in Kota Bharu, Kelantan. Internet usage is growing over time and as a result of its excessive use could lead to an addiction.A survey is conducted in Kota Bharu, Kelantan engaging respondents in a total of 422 secondary school students in the age range from 13 to 19 years old in answering the questionnaire provided related to this research. The level of Internet addiction is assessed by the Internet Addiction Test (IAT). The researchers chosea quantitative research method and results were analyzed by descriptive analysis. The results indicated, only 2.0% of respondents had experienced the high level of Internet addiction whereas the majority of respondents possess a low level of Internet addiction with a percentage of 64.0%. Responsible authorities must insert labor efforts in ensuring parents, teachers and adolescents are conscious about the alarming perils of IA. This study is expected to assist future research and current efforts to combat IA among secondary school students.